Ongoing controversies and recent insights of the ARMS2-HTRA1 locus in age-related macular degeneration. (September 2021) - May, Adam; Su, Fei; Dinh, Brian; Ehlen, Rachael; Tran, Christina; Adivikolanu, Harini; Shaw, Peter X.
Abstract: Age-related macular degeneration (AMD) is the most common cause of central vision loss among elderly populations in industrialized countries. Genome-wide association studies have consistently associated two genomic loci with progression to late-stage AMD: the complement factor H (CFH) locus on chromosome 1q31 and the age-related maculopathy susceptibility 2-HtrA serine peptidase 1 (ARMS2-HTRA1) locus on chromosome 10q26. While the CFH risk variant has been shown to alter complement activity, the ARMS2-HTRA1 risk haplotype remains enigmatic due to high linkage disequilibrium and inconsistent functional findings spanning two genes that are plausibly causative for AMD risk. In this review, we detail the genetic and functional evidence used to support either ARMS2 or HTRA1 as the causal gene for AMD risk, emphasizing both the historical development and the current understanding of the ARMS2-HTRA1 locus in AMD pathogenesis. We conclude by summarizing the evidence in favor of HTRA1 and present our hypothesis whereby HTRA1-derived ECM fragments mediate AMD pathogenesis. Highlights: The source of AMD pathogenicity at the ARMS2-HTRA1 locus is still unclear. ARMS2 is a secreted protein and may activate the complement system in the choroid. HTRA1 cleaves many extracellular matrix proteins and may be upregulated in AMD. Recent studies support a role for ECM fragments in mediating AMD pathogenesis.